Analysis of Fund Management on Prucinta Products at PT. Prudential Syariah Binjai - Ervina Yulia Angkat; Fauzi Arif Lubis (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
PRUCINTA is a traditional sharia life insurance productwith a membership period of 20 years that provides comprehensive protection against the risk of death and death due to accidents. In addition to protection for 20 yers, this product can also be extended without a medical examination, benefits in the form of cash value will be charged to the cash value fund at the end of the membership periode, and other benefits including protection against the risk of death. There may be an accident during the return period or due to the risk of returning. A complete explanation of fund management refers to the general anda specific provision of PRUCinta. Fund management for this PRUCinta product 100% Tabarru fund insurance compensation and the cash value of the cash value fund if the insurade participant dies during the membership period. This study aims to find out how to manage PRUCinta product funds at PT Prudential Syariah